Single-molecule super-resolution imaging by tryptophan-quenching-induced photoswitching of phalloidin-fluorophore conjugates - Nanguneri, Siddharth; Flottmann, Benjamin; Kuner, Thomas (Microscopy research and technique, 2014)
Photophysical properties of any fluorophore are governed by the chemical nanoenvironment. In the context of imaging biological samples, this translates to different photophysical properties for different labels and probes. Here, we demonstrate that the nanoenvironment of fluorophores within a probe can be advantageously used to induce particular properties such as light-induced photoswitching. We demonstrate efficient photoswitching and single-molecule super-resolution imaging for various fluorophore-phalloidin conjugates in aqueous buffer without the addition of further chemicals. We further demonstrate the utility of two-color imaging of fluorophore-phalloidin and a photoactivatable fluorescent protein in presynaptic nerve terminals.